Describing Family Needs within Adult Critical Care Units at a Military Hospital in Jeddah, Saudi Arabia (International Journal of Studies in Nursing, 2017)
Background: Family members have traumatic experiences when a loved one is admitted into critical care units as they are not psychological prepared for the sudden illness of a loved one. Attending to the needs of family members of critically ill patients is vital in providing appropriate holistic care for both the patient and the family. Methods: A cross sectional descriptive quantitative research design was used. The study was conducted in a military hospital in Jeddah, Saudi Arabia, within 10 critical care units. A total of 25 doctors, 66 critical care nurses and 38 family members were included in the study. Data was collected using the Critical Care Family Needs Inventory (CCFNI), a Likert tool developed by Jane Leske which has established reliability of 0.80-0.97. Findings: The most important need as perceived by doctors was “the “need to know the expected outcome’ regarding the patient’s condition, M= 3.72 (SD = 0.54), while critical care nurses’ perceived the most important family need as “To have explanations of the environment before going into the critical care unit for the first time, M= 3.65 (SD= 0.54). Further to this, family members’ perceived “To be assured that the best care possible is being given to the patient” as the most important family need M= 3.76 (SD= 0.54). Conclusion: Health care professionals have a responsibility towards meeting these needs in order to provide care that is holistic in nature that encompasses the basic tenets of patient-family centered care.